The Modifications of the Anterior Cruciate Ligament Rupture Physical Therapy Caused by the Anterolateral Ligament Injury - Kostrub, O.; Kotiuk, V.; Blonskyi, R.; Sushchenko, L.; Kachur, Y.; Kopochynska, Y.; Doroshenko, E. Yu.; Дорошенко, Едуард Юрійович (My University, 2021)
The anterolateral ligament (ALL) is a rotational stabilizer of the knee joint widely investigated the last 13 years as the possible cause of some anterior cruciate ligament (ACL) reconstructions failure. ALL injuries accompany 64% of ACL ruptures. Nevertheless, there are still no publications concerning changes in the ACL rehabilitation process due to the ALL concomitant rupture. We evaluated rotational stability in 12 athletes with the ACL rupture and concomitant ALL injury or Segond fracture treated conservatively before the treatment and 3 months later. The physical therapy comprised the range of motions and strengthening exercises during the immobilization period and thereafter. As only the knee joint was immobilized the physical therapy was conducted to the adjacent joints and muscles at the very beginning. A total of 83.33% of patients became pivot-shift negative in three months. In 16.67% pivot-shift test was questionable. Lachman test remained positive in 91.67%. The ACL is a more important structure than the ALL. So, our treatment strategy focuses mainly on it. Most changes in physical therapy are the immobilization and postponed axial loading with internal rotation. But even these minor changes may influence greatly the overall stability of the knee, particularly rotational stability. It seems to be the single case series assessing the rotational stability recovery after the ALL rupture conservative treatment we found in the scientific literature. Immobilization and non-weightbearing for up to 6 weeks may decrease the rotational instability in conservatively treated ALL injuries concomitant to the ACL ruptures. Further investigations of the physical therapy and rehabilitation of the anterolateral ligament injuries and Segond fractures are necessary.
Keywords: anterolateral ligament; anterior cruciate ligament; rehabilitation